A study of various image processing techniques - Liu, Rui. (2008)
In a Package Visual Inspection (PVI) system, the image processing technology is the key to successful inspection. In image processing, the image quality depends on several important factors including digital camera, lens, illuminating techniques, detected object characteristics. But in the manufacturing process, most of the engineers rely on their own experience or guess work. This dissertation discusses above factors that affect performance in the image processing.